Análisis financiero en la Cooperativa de Transportes Loja, periodos 2021-2022 - Vargas Sánchez, Bayron Andrés (2024)
The Work of Curricular Integration called: Financial Analysis in the Cooperativa de Transportes Loja, periods 2021-2022, was developed with the purpose of knowing the economic and financial situation of the cooperative, by means of a financial analysis applied to the financial statements to subsequently disclose the results obtained and contribute relevant information for better decision- making. In order to fulfill the first objective, the vertical and horizontal analysis was applied to determine the financial and economic structure of the cooperative, as well as the variations in the accounts that comprise them. As a result, the most representative account of Assets corresponds to Accounts and Documents Receivable Short Term. Liabilities represented by accounts payable. The Patrimony represented by the Social Capital. Revenues generated mainly from Sale of Services. Costs for Cost of Sales of Services rendered and Expenses represented by General Expenses and Services. The application of the horizontal analysis showed that the Assets decreased by $52,130.18 mainly due to a greater depreciation of property, plant and equipment. Liabilities, reveal an increase of $1,108,171.98 which is mainly attributed to the implementation of transitional accounts payable new quotas. The Patrimony shows a decrease of $-1.160.302,16 that is due to a proportion taken from the contribution of members of the cooperative. Revenue increased by $7,268,539.54 due to increased service sales. Costs and Expenses increased by $5,470,970.56 and $1,977,592.95 due to increased service costs and overhead and service costs. With the application of the financial indicators it was possible to identify ratios that present problems and do not reach the optimal standard as they are: Rotation of accounts receivable in 2021 with 3.17 times and in 2022 with 3.89 times, being below the standard indicating that it must rotate 6 to 12 times; Rotation of accounts payable, in 2021 rotated in 3.27 times and in 2022 in 3.66 times, being below optimal which indicates that it must rotate 6 to 12 times; External leverage represented a value of $0.63 in 2021 and $0.71 in 2022, being optimal that is less than $0.50; Internal leverage in 2021 was $0.37 and in 2022 $0.29 disclosing that it is below the standard that indicates that it must be greater than 1; Profitability on sales presented in 2021 a percentage of 0.08% and in 2022 -0.55%, revealing that the standard is greater than 1% and Profitability on assets in 2021 was 0.14% and in 2022 -1.21%, being the optimal average 5%. To fulfil the third objective, the financial report was prepared on the basis of the results obtained from the implementation of the financial analysis, where a synthesis of the results obtained is presented, as well as conclusions and recommendations to improve decision-making related to the financial and economic situation and thus contribute to the improvement and growth of the Cooperativa de Transportes Loja.